Anak Tak Sah Taraf dan Kesannya Kepada Status Agama: Kajian Kes Rosliza Ibrahim - Dzafir Firdaus Ahmad Zubairy; Mohd Hanafiah Abdullah; Muhammad Nur Akmal Abdul Samad; Ahmad Mukhlis Jahani; Muhammad Mutmain Ramlan; Nisar Mohammad Ahmad (Centre of Research for Fiqh Forensics and Judiciary (CFORSJ), Universiti Sains Islam Malaysia, 2025)
INTERNATIONAL CONFERENCE ON SYARIAH, LAW AND SCIENCE 2024 (CFORSJ i-CONF 2024) 7 November 2024 - 30 November 2024 Editorial Team: Wan Abdul Fattah Wan Ismail, Lukman Abdul Mutalib, Zulfaqar Mamat, Aspalilah Alias, Hasnizam Hashim, Ahmad Syukran Baharuddin, Muhammad Aniq Aiman Alias, Tuan Mohd Faris Hamzi Tuan Ibrahim, Radin Ahmad Taufik Salikin Izzaddin, Ahmad Salman Mohd Yusof. Organized : Centre of Research for Fiqh Forensics and Judiciary (CFORSJ), Faculty of Syariah and Law, USIM